Access to public sports infrastructure in Poland as a preventive factor for cardiovascular diseases - Jasiura, Adam; Lipczyńska, Wiktoria; Warchoł, Konrad; Gorzel, Mateusz (Journal of Education, Health and Sport, 2023)
Introduction: Cardiovascular diseases (CVDs) are a significant health concern globally, including in Poland. Physical activity has been identified as a crucial preventive factor for CVDs, and access to public sports infrastructure plays a vital role in promoting physical activity. However, the relationship between access to such infrastructure and its impact on cardiovascular health outcomes in Poland remains understudied. Aim of the study: This study aims to investigate the impact of access to public sports infrastructure on the prevalence of cardiovascular diseases and mortality rates in Poland. Materials and methods: Publicly available data were obtained regarding sports facilities, population structure, hospitalizations, and deaths. Results: There is a moderate negative correlation (r = -0.3096; p < 0.001) between hospitalization rates for cardiovascular diseases and the stadiums and playing fields available in the studied countries. The correlation between cardiovascular hospitalizations and indoor and outdoor arenas and gyms was also negative, but its effect was moderately weak (r = -0.2068, p < 0.001; r = -0.2597, p < 0.001, respectively). The average hospitalization rate for cardiovascular diseases in subjects over 65 years of age (M = 12117.24) was significantly higher compared to the group of all subjects (M = 3082.18) and subjects under 65 years of age (M = 1260.96). There is a negative correlation between the death rate and the availability of selected sports facilities, with a moderately weak effect for all sports infrastructure subgroups (r = -0.215 - -0.233). Conclusion: The effect of accessibility to public sport infrastructure on CVDs prevalence and related deaths is moderate to weak. The studied positive effect particularly affects people under 65 years of age. Further studies of other sport-connected predictors may be beneficial.